Bali Aga Villages Documentation in Bangli Regency as Architectural Conservation and Cultural Heritage - Ni Made Yudantini (Journal of Architecture & Environment, 2022)
The Island of Bali is not only rich in natural conditions and landscapes but also has unique socio-cultural and architectural characteristics. This makes the island of Bali a tourism and research destination, especially the indigenous villages that are called Bali Aga. There are approximately twenty-five villages spread and lies on in the four areas of the Bangli Regency. These Bali Agavillages are unique for implementing the original Balinese traditions. Mostly the Bali Aga villages take place in the fringe ofmountains, hilly areas, and along the shores of Lake Batur. The observations on the architecture of the houses found that there arefew traditional buildings called sakaroras still extant. This cannot be separated from technological and communication developments that affect people's lives. The study aims to explore the existence of the indigenous villages in the Bangli Regency,mainly to document the architecture of traditional houses that still exist. Observations were carried out to obtain primary data regarding the architectural conditions of the sakaroras. Interviews were conducted with the village leader to get information aboutthe history, the village’s needs, and the sakaroras house condition. This study found that most sakaroras houses have been turned into a modern house style. This research implies that it is essential to document the existence of the sakaroras place, which tends to change as evidence of cultural heritage and the identity of traditional Balinese architecture. Public awareness to maintaincultural heritage needs to be encouraged through programs to foster the importance of preserving traditional houses.